Interrogating the transmission dynamics of Trypanosoma cruzi (Trypanosomatida, Trypanosomatidae) by Triatoma venosa (Hemiptera: Reduviidae) after the elimination of vector transmission by Rhodnius prolixus in Boyacá eastern Colombia - Medina, Manuel; Zuluaga, Sara; Martínez, María Fernanda; Bermúdez, Juan Carlos; Hernández, Carolina; Beltrán, Virgilio; Velásquez-Ortiz, Natalia; Muñoz, Marina; Ramírez, Juan David; Triana, Omar; Cantillo-Barraza, Omar (Frontiers in Cellular and Infection Microbiology, 2022)
Chagas disease (CD) is a parasitic zoonosis (Trypanosoma cruzi) that is endemic in Colombia. Vector control of Rhodnius prolixus, the main domestic T. cruzi vector, has been achieved in a large part of the area with historically vector transmission of CD. . It is necessary to understand the ecological behavior characteristics of local native vectors to ensure sustainability of the vector control programs. To evaluate the long-term success of a recent vector control campaign in the Boyacá department (Colombia), we used a combined strategy of entomological surveillance with co-existing canine surveillance from ten rural villages within six municipalities of the Tenza valley region (Boyacá, Colombia): Chinavita, Garagoa, Guateque, Somondoco, Sutatenza and Tenza, with historical reports of R. prolixus and secondary vectors. Collected triatomines and canine whole blood were analyzed for T. cruzi infection and genotyping. Triatomine bugs specimens were evaluated for blood meal source. Canine serology was performed using two distinct antibody assays. In total, 101 Triatoma venosa were collected by active search in domestic and peridomestic habitats. A natural infection prevalence of 13.9% (14/101) and four feeding sources were identified: human, dog, rat, and hen. A frequency infection of 46.5% (40/87) was observed from two independent serological tests and T. cruzi DNA was detected in 14 dogs (16.4%). Only TcIsylvatic DTU was detected. The results suggest that T. venosa present eco-epidemiological characteristics to maintain the transmission of T. cruzi in Tenza valley. This species has reinfested the intervened households and it has an active role in domestic and peridomestic transmission of T. cruzi due to their infection rates and feeding behavior. Therefore, this species should be considered as epidemiologically relevant for vector control strategies. Moreover, there is a need for human serological studies to have a close up of risk they are exposed to.